Europe and Central Asia Economic Update, Spring 2021 : Data, Digitalization, and Governance - World Bank (Washington, DC: World Bank, 2021)
Governments play a critical role in the economies of Europe and Central Asia, where government expenditures are close to 40 percent of gross domestic product and the public sector accounts for nearly 27 percent of total employment, which is almost twice the global average. The public sector often attracts some of the best educated workers in the region. And support for a larger public sector is increasing due to aging populations and their growing health care and long-term care needs, rising inequality and greater support for redistribution, and increasing expenditures as governments address the challenges posed by the COVID-19 crisis. The significant role that government plays underscores the importance of the quality of governance in determining productivity and growth and effectively responding to the region’s economic and social challenges. Digital technology and the data revolution offer the potential to increase efficiency, transparency, responsiveness, and citizen trust, directly impacting the quality of government. Across the world, the quality of government is increasingly informed by the extent to which governments harness digital tools and GovTech to optimize management, service delivery, and overall state capacity. Technology and data are also key for fostering collaboration between governments and civil society to improve public sector efficiency and service delivery. The COVID-19 pandemic has highlighted the costs associated with delaying digitalization and GovTech implementation and the opportunities that lie in public sector modernization.